Employee Performance Analysis Based on Compensation, Motivation and Work Environment at PT Support Logistic Indonesia - Firly Dwi Rochmah; Jojok Dwiridotjahjono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the impact of compensation, motivation, and work environment on employee performance at PT Support Logistic Indonesia. A quantitative approach is applied using a survey method, with data collected through questionnaires and analyzed using multiple linear regression. The results show that compensation, motivation, and work environment collectively have a significant effect on employee performance. Partially, compensation and work environment significantly influence performance, while motivation has no impact. These findings suggest that enhancing employee welfare through fair compensation policies and fostering a conducive work environment can optimize employee performance.